استخدام الرقمنة الضريبية في تحقيق الاصلاح الضريبي في العراق (Journal of Accounting and Financial Studies ( JAFS ), 2024)
In light of modern technological development, digital transformation has become an influential factor in all fields and has played a major role in developing the administrative apparatus of countries, due to the successes it has achieved at the economic level. Many countries have taken tax digitalization to achieve tax reform to reduce tax avoidance, and tax evasion, and increase tax collection. The main objective of this research is to study the experiences undertaken by some Arab countries for tax reform in the field of using digitization in the tax field and to benefit from the lessons of these countries, as the research was launched to address a problem that is the weakness of the use of tax digitization in the tax field, and from here comes the importance of the research to study the experiences Some countries have relied on modern technological means and the use of tax digitization to achieve tax reform. The research reached several conclusions, the most important of which is that tax employees enjoy wide freedom in estimating the tax, and the tax legislation in force suffers from some defects that make compliance with and application of it almost impossible. On the other hand, the most important recommendation was to provide the necessary infrastructure to use digitization in tax collection and train cadres on Dealing with them and preparing a fair, simple, and effective tax system that contributes to achieving the objectives of tax policy.